2019
DOI: 10.14254/2071-8330.2019/12-3/16
|View full text |Cite
|
Sign up to set email alerts
|

Overdue debt and selected personality traits – a research based on international surveys

Abstract: Households and individuals make various financial decisions, some of which are regarding debt. In 2018 a survey was conducted in six European countries on incurring financial liabilities and falling into debt. The survey was expected to provide insights as to the habits and attitudes of the surveyed while making debt decisions. The aim of this paper is to identify personal characteristics of debtors across different European countries and to compare the incidence of these characteristics in the groups examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…It could also be interesting to verify if there is a similar relationship between going bankrupt and the indicated variables if the variable is not the self-estimation of probability of bankruptcy but the real state of falling into bankruptcy as it was shown that sometimes being optimistic about future means falling into problems (see e.g. Forlicz, Rólczyński, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It could also be interesting to verify if there is a similar relationship between going bankrupt and the indicated variables if the variable is not the self-estimation of probability of bankruptcy but the real state of falling into bankruptcy as it was shown that sometimes being optimistic about future means falling into problems (see e.g. Forlicz, Rólczyński, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Digitalization can also influence the testing of average price reversals for agricultural products. Factors such as overdue debt and individual personality traits can also change the situation [26,27,28,29].…”
Section: Source: Composed By Authorsmentioning
confidence: 99%
“…On the extreme end is over-indebtedness, which typically suggests difficulties to meet debt payment obligations, and has both been linked with depressive symptoms and sleeping difficulties [ 50 ]. With regards to personality traits, it has been shown that individuals with low levels of dutifulness or conscientiousness [ 51 ] and a propensity towards neuroticism and feelings of guilt [ 52 ] are more likely to experience over-indebtedness. Impulsivity has also been linked to both indebtedness behavior [ 53 ] and over-indebtedness [ 54 ].…”
Section: Introductionmentioning
confidence: 99%